The gentle art of swedish death cleaning eaudiobook How to free yourself and your family from a lifetime of clutter. - Magnusson, Margareta (Simon & Schuster Audio, 2018)
*The basis for the wonderfully funny and moving TV series developed by Amy Poehler and Scout Productions* A charming, practical, and unsentimental approach to putting a home in order while reflecting on the tiny joys that make up a long life. In Sweden there is a kind of decluttering called döstädning , dö meaning "death" and städning meaning "cleaning." This surprising and invigorating process of clearing out unnecessary belongings can be undertaken at any age or life stage but should be done sooner than later, before others have to do it for you. In The Gentle Art of Swedish Death Cleaning , artist Margareta Magnusson, with Scandinavian humor and wisdom, instructs readers to embrace minimalism. Her radical and joyous method for putting things in order helps families broach sensitive conversations, and makes the process uplifting rather than overwhelming. Margareta suggests which possessions you can easily get rid of (unworn clothes, unwanted presents, more plates than you'd ever use) and which you might want to keep (photographs, love letters, a few of your children's art projects). Digging into her late husband's tool shed, and her own secret drawer of vices, Margareta introduces an element of fun to a potentially daunting task. Along the way readers get a glimpse into her life in Sweden, and also become more comfortable with the idea of letting go.